Leading Article - Mahattanatawee, Kanjana (Journal of Food Technology, Siam University, 2020)
Journal of Food Technology, Siam University has been published with the objective to disseminate research and service to society. Every article has been considered and proved by experts in the relevant fields from many educational institutions. The editorial board hopes that readers will gain useful academic knowledge and can be used as a reference for later.